Data Collection In Sociolinguistics: Methods and Applications - Mallinson, Christine , Childs, Becky and Van Herk, Gerard (London: Routledge, 2018)
This book provide up=to-date, succinct, relevant and informative discussion about methods of data collection in sociolinguistic research. It covers the main areas of research design, conducting research, and sharing data and findings.
Includes Bibliographic references and index.
Keywords: Sociolinguistics Research--Qualitative Research--Linguistic Landscape Research-- Forensic Linguistics Data Collection